Tecnologie per la Sostenibilità negli Ambienti Fragili: Il fotovoltaico invisibile: tegole fotovoltaiche integrate nel paesaggio (Archeomatica, 2024)
Sharing the goal of reducing greenhouse gas emissions into the atmosphere to levels that prevent the temperature rise by 1.5 C by 2050 requires responsible behaviour and important decisions to pursue sustainable development. There are many definitions that are given to the word sustainability: starting from a vision initially focused mainly on ecological aspects, we have moved on to an approach that from the environmental level considers also the economic and social one. The replacement of fossil fuels with renewable energy sources is one of the pillarscof a strategy aimed at sustainability. Among them, solar and in particular phovoltaic Energy already responds to the repalacement of significant shares of fossil fuels.Photovoltaic panels are appearing more and more often on the roofs of buildings and are able to cover a large part of the energy consumption of users. On the other hand, the need to have important surfaces for installation and the considerable visual impact, prevents its use in fragile landscape contexts such as those of our villages and historic centers.The dilemma between energy production from renewable sources and fragile landscapes can be solved with the use of photovoltaic panels with zero visual impact such as those produced by the company Dyaqua, which has been experimenting and producing patented components for "invisible photovoltaics"